Cultivation Model of Interfaith Harmony Social Institutions (Case Study of Religious Harmony Forum in Mojorejo Village, Bumiaji District, Batu City) - Wahyudi,; Mohammad Jafar Loilatu,; Wahyudi, Fidela Dzatadini (Technium Social Sciences Journal, 2025)
The dynamics of community diversity with various religious backgrounds that repeatedly become increasingly tense show that building harmony between religious communities is a fundamental challenge in a multicultural society. This article examines a model that can be used as a formulation of inter-religious harmony, which is described from history to the implementation of the model of cultivation of social institutions of harmony at the community level, especially in Mojorejo Village, Bumiaji District, Batu City. This research uses qualitative research. The results of this study show that interfaith harmony is built using three main basic principles, namely the internalization of social values and norms about tolerance, strengthening social institutions, and creating open spaces for interfaith community interaction. By building systematic and community-based social institutions, it can make the cultivation model of interfaith harmony not only a formal norm, but also a community identity in diversity.